Child sexual exploitation material offenders, one‐size‐fits‐all for? Exploring tailored clinical dimensions based on cognitive and behavioural criminogenic factors. (20th April 2022) - Paquette, Sarah; Chopin, Julien; Fortin, Francis
Abstract: Background: Interventions for individuals involved in sexual offending behaviours are likely to be more effective if adapted to focus on their specific characteristics, suggesting that men who engage in sexual offences against children over the Internet should be treated differently from those who have actual physical contact against children. Aims: The goal of this study is to explore possible associations between the criminogenic cognitions and behaviours of men using online child sexual exploitation material (CSEM) and variables relevant to intervention. We hypothesised that antisocial tendencies, sexual, emotional and relational problems and self‐regulation problems, as well as cognitive distortions would be associated with CSEM use. Method: Ninety‐eight men who had been convicted of at least one online CSEM‐related offence, but no child contact sexual offences, at any time between 2001 and 2020 were recruited in the province of Quebec (Canada). Cases were reviewed to identify cognitive and behavioural criminogenic factors according to a coding sheet developed after reference to prior literature. Variables were extracted from official criminal records, sexological and psychological reports, as well as investigative and forensic reports and interviews. Exploratory factor analysis was carried out to identify potentially relevant dimensions. Results: Analysis confirmed five distinct factors which, together, accounted for 60% of the variance: dissocial traits, dysfunctional intimacy, passive alienation (internalised sense of alienation), normless alienation (social norms experienced as alien) and coping with threat . Conclusion: Because online CSEM‐related offenders present heterogeneous risks and needs, a 'one‐size‐fits‐all' intervention is unlikely to be optimal for most of them. Our findings suggest a way of classifying risks and needs to facilitate more focused interventions. Future research should evaluate the relative effectiveness of general interventions compared to those tailored towards the dimensions of risks and needs identified in this study.